Verdauungsoptimierung – wie sich Ernährung und Mikrobiom gegenseitig beeinflussen - Bischoff, Stephan C. (DMW - Deutsche Medizinische Wochenschrift, 2019)
Nutrition affects intestinal bacteria by stimulating the expansion of bacteria that can metabolize the nutrient components offered. Conversely, gut bacteria help to optimize food digestion and increase energy intake. Thus, the intestinal microbiome is regulated primarily by nourishment: it determines the composition, function and diversity of the microbiome. As a result, the intestinal microbiome helps to optimize energy and substrate production from food. This is beneficial in cases of imminent malnutrition, but can be detrimental in case of overeating and obesity.
Keywords: Ernährung; Adipositas; Unterernährung; Darm-Mikrobiom; PNALD